Niños : poems for the lost children of Chile - Ferrada, María José, 1977- (Eerdmans Books for Young Readers, 2021)
A collection of illustrated poems written in tribute to the thirty-four children--younger than fourteen--whose lives were lost or who were merely listed missing in the wake of Augusto Pinochet's dictatorial regime in Chile.